SURGICAL TREATMENT OF PREMATURE EJACULATION, ASSOCIATED WITH SHORT FRENULUM OF PENIS - N. D. Akhvlediani (Сеченовский вестник, 2010)
Aim. Assessment of efficacy of frenuloplasty modifications in patients with premature ejaculation, associated with short frenulum of penis.Methods. Prospective study included 68 patients with primary premature ejaculation, associated with short frenulum of penis. 1st group consisted of 33 patients (age 20,4±3,7 years), in whom standard frenuloplasty was performed. 2nd group included 35 patients (age 21,9±4,6 years) in whom z-shaped frenuloplasty was performed. Before and in 1 month after start of sexual life premature ejaculation profile (PEP) questionnaire was used, time of intravaginal delay of ejaculation was measured, vibration sensitivity of penis was determined. All patients by themselves measured changes of ejaculation after treatment.Results. PEP values become sighnificantly better in both treatment groups (/><0,001), but in 2nd groups parameters of 1-4 questions were higher (/><0,001). Time of intravaginal delay of ejaculation increased in both groups (69,9±22,8 and 360,3± 125,5 sec; /><0,001 in 1st; 68,5+21,4 and 355,1 ± 124,3 sec; /><0,001 in 2nd). Vibration sensitivity of penis also significantly increased in both groups (/><0,001). Glandular tactile sensitivity threshold increased more significantly in patients, undergone z-shaped frenulopalsty. Self measures changes of ejaculation after treatment were more prominent in patients, undergone z-shaped frenulopalsty (2,3+0,7 vs 1,8±0,8 points, /7=0,032).Conclusion. Z-shaped frenuloplasty is one of the most effective approaches to treatment of premature ejaculation, associated with short frenulum of penis.